Emerging treatment options for the treatment of moderate to severe plaque psoriasis and psoriatic arthritis: evaluating bimekizumab and its therapeutic potential - Chiricozzi A; De Simone C; Fossati B; Peris K (Dove Medical Press, 2019)
Andrea Chiricozzi,1,2 Clara De Simone,1,2 Barbara Fossati,2 Ketty Peris1,21Institute of Dermatology, Catholic University, Rome, Italy; 2Fondazione Policlinico Universitario A. Gemelli IRCCS, Rome, ItalyAbstract: Plaque psoriasis (PsO) is a chronic inflammatory skin disorder that may be associated with several comorbidities, including arthritis. The increasing knowledge of psoriasis pathogenesis led to the identification of novel targeted therapeutic interventions. Among them, anti-IL-17A and anti-IL-17F antibodies are currently being investigated for the treatment of PsO and/or psoriatic arthritis (PsA). Bimekizumab is one of these agents, capable ofsimultaneously neutralizing both IL-17A and IL-17F cytokines. In this review we included preclinical and clinical data related to this highly promising agent that shows a peculiar molecular structure differing from other bispecific agents.Keywords: psoriasis, psoriatic arthritis, bimekizumab, bispecific agent, dual specific agent